Current Management and Treatment of Infantil Hemangiomas - Özkiliç, Alper; Solgun, Hüseyin Avni (Highlights on Medicine and Medical Science Vol. 16, 2021)
Infantile hemangiomas are the most common vascular tumors of infancy, affecting up to 12% of infants by the first year of life. Infantile hemangioma develops during the first weeks of life, usually builds up over 3 to 6 months, and then regresses very slowly over a period of 3 to 7 years. Three quarters of these hemangiomas are lobular and are not associated with malformations. On the other hand, the hemangiomas referred to as segmental may be associated with developmental abnormalities (PHACES and PELVIS/SACRAL syndromes). The majority of infantile hemangiomas require no treatment. In 10 to 15% of cases, treatment options include oral propranolol, topical timolol, and oral corticosteroids. Indications for active intervention include hemorrhage unresponsive to treatment, impending ulceration in areas where serious complications might ensue, interference with vital structures, life- or function-threatening complications, and significant disfigurement. Treatment should be individualized, depending upon the size, rate of growth, morphology, number, and location of the lesion (s), existing or potential complications, benefits and adverse events associated with the treatment, age of the patient, level of parental concern, and the physician's comfort level with the various treatment options.